Developmental regulation of group I metabotropic glutamate receptors in the premature brain and their protective role in a rodent model of periventricular leukomalacia - JANTZIE, LAUREN L. (Neuron Glia Biol, 2011)
Cerebral white matter injury in premature infants, known as periventricular leukomalacia (PVL), is common after hypoxia- ischemia (HI). While ionotropic glutamate receptors (iGluRs) can mediate immature white matter injury, we have previously shown that excitotoxic injury to premyelinating oligodendrocytes (preOLs) in vitro can be attenuated by group I metabotropic glutamate receptor (mGluR) agonists. Thus, we evaluated mGluR expression in developing white matter in rat and human brain, and tested the protective efficacy of a central nervous system (CNS)-penetrating mGluR agonist on injury to developing oligodendrocytes (OLs) in vivo. Group I mGluRs (mGluR1 and mGluR5) were strongly expressed on OLs in neonatal rodent cerebral white matter throughout normal development, with highest expression early in development on preOLs. Specifically at P6, mGluR1 and mGLuR5 were most highly expressed on GalC-positive OLs compared to neurons, axons, astrocytes and microglia. Systemic administration of (1S,3R) 1-aminocyclopentane-trans-1,3,-dicarboxylic acid (ACPD) significantly attenuated the loss of myelin basic protein in the white matter following HI in P6 rats. Assessment of postmortem human tissue showed both mGluR1 and mGluR5 localized on immature OLs in white matter throughout development, with mGluR5 highest in the preterm period. These data indicate group I mGluRs are highly expressed on OLs during the peak period of vulnerability to HI and modulation of mGluRs is protective in a rodent model of PVL. Group I mGluRs may represent important therapeutic targets for protection from HI-mediated white matter injury.